An Analysis of High School Transformation Effort from an Outcome Perspective - Hea-Jin Lee; S. Asli Ãzgün-Koca; Dean Cristol (Arizona State University, 2011)
This study investigates the effectiveness of the Ohio High School Transformation Initiative using several years of state data on attendance, graduation, dropout rates, and performance index scores. Results indicate differences between small schools or small learning communities, and traditional schools that have similar school profiles to small schools in: graduation rates by year; attendance rates among the traditional schools over the years; and the performance index scores. Small schoolsâ performance index scores gradually increased, but traditional schools with similar school profiles outperformed small schools. There was no difference in the dropout rates. Creating a sense of community, rather than simply transforming the school structure, seems to be the key to improving high school education.